Systemic inflammation mediates environmental polycyclic aromatic hydrocarbons to increase chronic obstructive pulmonary disease risk in United States adults: a cross-sectional NHANES study - Xiao, Yingqi; Zhang, Li; Liu, Hu; Huang, Wei (Frontiers in Public Health, 2023)
Introduction This study explored the relationship between environmental polycyclic aromatic hydrocarbons (PAHs) and Chronic obstructive pulmonary disease (COPD), and identified systemic inflammation as a mediator of the increased risk of COPD from PAHs. Methods Data were obtained from 60,936 middle-aged and older Americans recruited in the National Health and Nutrition Examination Survey 2005–2016. Environmental PAHs were measured in terms of urinary concentrations of PAHs metabolites (NAP: 1-hydroxynaphthalene, FLU: 2-hydroxyfluorene, PA: 1-hydroxyphenanthrene, and PYR: 1-hydroxypyrene). We used multifactor logical analysis to figure out the link between PAHs and COPD, and the non-linear relationship was examined using Restricted cubic spline. Spearman correlation analysis was utilized to analyze the connection between PAHs and systemic immune-inflammation index (SII). Results The results showed that the COPD population had higher NAP (3.550 vs. 3.282, p < 0.001), FLU (2.501 vs. 2.307, p < 0.001), PA (2.155 vs. 2.082, p = 0.005), and PYR (2.013 vs. 1.959, p = 0.008) levels than non-COPD population. In unadjusted logistics analysis, the risk of COPD with log NAP was higher [OR = 1.461, 95% CI (1.258–1.698), p < 0.001]. Upon taking into account, confounders like sex, age, race, and log NAP still increased a possible COPD risk [OR = 1.429, 95% CI (1.224–1.669), p < 0.001]. Similarly, FLU, PA, and PYR significantly increased the risk of COPD (all OR > 1, p < 0.05), both unadjusted and adjusted. Furthermore, Restricted cubic spline demonstrated a strong link between PAHs levels and COPD risk (p < 0.05). Additionally, a Spearman correlation analysis revealed a favorable association between log FLU and log SII (R = 0.43, p = 0.006), while NAP, PA, and PYR levels were not associated with log SII (all p > 0.05). Ultimately, the mediating effect analysis revealed a mediating effect capacity of 5.34% for the SII-mediated association between FLU and COPD. Conclusion The findings suggest that the risk of COPD is significantly increased when environmental PAHs exposure is at high levels, and that systemic inflammation may be involved in the process.